The Syabru‐Bensi hydrothermal system in central Nepal: 1. Characterization of carbon dioxide and radon fluxes. Issue 5 (12th May 2014) - Girault, Frédéric; Perrier, Frédéric; Crockett, Robin; Bhattarai, Mukunda; Koirala, Bharat Prasad; France‐Lanord, Christian; Agrinier, Pierre; Ader, Magali; Fluteau, Frédéric; Gréau, Claire; Moreira, Manuel
Abstract The Syabru‐Bensi hydrothermal system (SBHS), located at the Main Central Thrust zone in central Nepal, is characterized by hot (30–62°C) water springs and cold (<35°C) carbon dioxide (CO2) degassing areas. From 2007 to 2011, five gas zones (GZ1–GZ5) were studied, with more than 1600 CO2 and 850 radon flux measurements, with complementary self‐potential data, thermal infrared imaging, and effective radium concentration of soils. Measurement uncertainties were evaluated in the field. CO2 and radon fluxes vary over 5 to 6 orders of magnitude, reaching exceptional maximum values of 236 ± 50 kg m−2 d−1 and 38.5 ± 8.0 Bq m−2 s−1, with estimated integrated discharges over all gas zones of 5.9 ± 1.6 t d−1 and 140 ± 30 MBq d−1, respectively. Soil‐gas radon concentration is 40 × 103 Bq m−3 in GZ1–GZ2 and 70 × 103 Bq m−3 in GZ3–GZ4. Strong relationships between CO2 and radon fluxes in all gas zones (correlation coefficient R = 0.86 ± 0.02) indicate related gas transport mechanisms and demonstrate that radon can be considered as a relevant proxy for CO2. CO2 carbon isotopic ratios (δ13C from −1.7 ± 0.1 to −0.5 ± 0.1‰), with the absence of mantle signature (helium isotopic ratios R/RA < 0.05), suggest metamorphic decarbonation at depth. Thus, the SBHS emerges as a unique geosystem with significant deep origin CO2 discharge located in a seismically active region, where we can test methodological issues and our understanding of transport properties and fluid circulations in the subsurface.